PENGARUH DANA PIHAK KETIGA DAN PEMBIAYAAN PERBANKAN SYARIAH TERHADAP PERTUMBUHAN PRODUK DOMESTIK BRUTO DI INDONESIA - INDAH NURJANNAH, H. ABD. JALIL (Al-Mizan: Jurnal Ekonomi Syariah, 2021)
This study aims to determine the effect of third party funds and Islamicbanking financing on the growth of Gross Domestic Product (GDP) in Indonesia.This study uses quantitative analysis methods because the research data is in theform of numbers and the analysis uses statistics. Data on the development ofthird-party funds and Islamic banking financing as well as data on the growth ofGross Domestic Product (GDP) are data collected for this study sourced from theofficial website of the Central Statistics Agency (BPS). Data analysis usedmultiple linear regression statistics. Data processing uses the SPSS version 20application. The results of the study partially show that third party funds andIslamic banking financing have a positive and significant effect on GrossDomestic Product (GDP). Simultaneously, third party funds and Islamic bankingfinancing have a positive influence on Gross Domestic Product (GDP). Based onthe results of the R Square test, the magnitude of the influence of third party fundsand Islamic banking financing on Gross Domestic Product (GDP) is 98.2%